Bali Diaspora di Daerah Transmigrasi: Representasi Kearifan Lokal Bali di Kabupaten Bolaang Mongondow, Sulawesi Utara - Punia, I Nengah; Budi Nugroho, Wahyu (Jurnal Kajian Bali (Journal of Bali Studies), 2020)
This research aims to examine the representation of Balinese local wisdom in the daily life of Balinese transmigrants in Bolaang Mongondow Regency, North Sulawesi Regency. It also aims to analyse how the culture representation implicates the social interaction among the Bali diasporas with the local people and the transmigrants from other regions. This research using quantitative and qualitative approachs with questionnaire and interview as data collection instruments. The results shows that most of the local Balinese wisdom was still represented in the daily life of the Balinese transmigrant community in Bolaang Mongondow, except that the subak irrigation system and Balinese architecture were felt to be lacking.The interaction between Balinese transmigrants with local people and other transmigrants from other regions is very harmonious. It is caused the strengths of Balinese philosphies for instance Tri Hita Karana and Menyama Braya in the daily life of Balinese transmigrants in Bolaang Mongondow Regency, North Sulawesi Province. Keywords :  representation, local wisdom, Balinese transmigrant, Bolaang Mongondow Regency